2016
DOI: 10.1021/acs.langmuir.6b02513
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Adsorption, Reduction, and Polymerization of the Plutonyl(VI) and Uranyl(VI) Ions from Solution onto the Muscovite Basal Plane

Abstract: X-ray scattering techniques [in situ resonant anomalous X-ray reflectivity (RAXR) and specular crystal truncation rods (CTR)] were used to compare muscovite (001) surfaces in contact with solutions containing either 0.1 mM plutonyl(VI) or 1 mM uranyl(VI) at pH = 3.2 ± 0.2, I(NaCl) = 0.1 M, as well as in situ grazing-incidence X-ray absorption near-edge structure (GI XANES) spectroscopy and ex situ alpha spectrometry. Details of the surface coverage are found to be very different. In the case of Pu, alpha spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…17 Nanoparticle formation via hydrolysis has also been found to be an important process in the chemical and environmental behavior of highly radiotoxic Pu, 18,19 where it was found that the process is accelerated at mineral surfaces. 20,21 Aqueous Zr(IV) polymerization then is a promising model system for studying such multistep nanoparticle evolution processes, since Zr(IV), bearing a small ionic radius (0.75 Å) and high charge, is prone to hydrolysis in solutions leading to a progressive oligomerization that produces polydisperse Zr nanoparticles. Numerous studies have focused on Zr(IV) hydrolysis and oligomerization reactions in aqueous solutions to gain insights into the structural details of potential Zr(IV) building units as a function of solution chemistry using a variety of techniques, including X-ray absorption fine structure (XAFS) spectroscopy, 22−25 small (or wide)-angle X-ray scattering [S(W)AXS], 26−31 high-energy X-ray scattering (HEXS), 3 NMR/Raman spectroscopy, 3,23,32 electron-spray ionization mass spectrometry (ESI-MS), 25,33,34 dynamic light scattering (DLS), 24,35 transmission electron microscopy (TEM), 36 and Xray diffraction (XRD).…”
Section: − → − − + 2h O Zrmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Nanoparticle formation via hydrolysis has also been found to be an important process in the chemical and environmental behavior of highly radiotoxic Pu, 18,19 where it was found that the process is accelerated at mineral surfaces. 20,21 Aqueous Zr(IV) polymerization then is a promising model system for studying such multistep nanoparticle evolution processes, since Zr(IV), bearing a small ionic radius (0.75 Å) and high charge, is prone to hydrolysis in solutions leading to a progressive oligomerization that produces polydisperse Zr nanoparticles. Numerous studies have focused on Zr(IV) hydrolysis and oligomerization reactions in aqueous solutions to gain insights into the structural details of potential Zr(IV) building units as a function of solution chemistry using a variety of techniques, including X-ray absorption fine structure (XAFS) spectroscopy, 22−25 small (or wide)-angle X-ray scattering [S(W)AXS], 26−31 high-energy X-ray scattering (HEXS), 3 NMR/Raman spectroscopy, 3,23,32 electron-spray ionization mass spectrometry (ESI-MS), 25,33,34 dynamic light scattering (DLS), 24,35 transmission electron microscopy (TEM), 36 and Xray diffraction (XRD).…”
Section: − → − − + 2h O Zrmentioning
confidence: 99%
“…One component of such a system may be the formation of nanoparticles through the polymerization of metal cation hydrolysis species by olation () or oxolation (). The hydrolysis route as a facile pathway to the formation of nanoparticles has been demonstrated in recent work on Ce­(IV) . Nanoparticle formation via hydrolysis has also been found to be an important process in the chemical and environmental behavior of highly radiotoxic Pu, , where it was found that the process is accelerated at mineral surfaces. , …”
Section: Introductionmentioning
confidence: 99%
“…Vacancy shows as a dioctahedral structure in the octahedron sheet. Normally, the tri-layer structure is linked together by K þ ion via weak ionic bonds [50][51][52][53]. For strong assemblage of adjacent layers, it is non-expandable.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, partial Si atoms within the tetrahedron are substituted by Al atoms, yielding negative charges. 3 In order to balance these negative charges, partial cations such as K + or Na + ions exist in the interlayer, leading to an uneven distribution of charges. 3 In addition, a layered structure has numerous cavities trapping other species such as Fe 3+ or Fe 2+ ions, enhancing the uneven distribution of charges.…”
Section: Introductionmentioning
confidence: 99%
“…3 In order to balance these negative charges, partial cations such as K + or Na + ions exist in the interlayer, leading to an uneven distribution of charges. 3 In addition, a layered structure has numerous cavities trapping other species such as Fe 3+ or Fe 2+ ions, enhancing the uneven distribution of charges. In most of these cases, the interlayer only exudes the van der Waals force, resulting in the facile movement of the adjacent layers.…”
Section: Introductionmentioning
confidence: 99%